2010
DOI: 10.1002/etc.353
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of field and laboratory exposures of Lumbriculus variegatus to polychlorinated biphenyl-impacted river sediments

Abstract: A method is described for conducting 14-d in situ sediment bioaccumulation tests with the freshwater oligochaete Lumbriculus variegatus, at the bottom of a slow-flowing river. The in situ test exposure chambers were constructed from cylindrical plastic tubes with flow-through mesh screens and were attached to a wire basket that was weighted to the river bottom at seven sites in the lower Grasse River in New York State, USA. This design was successful in exposing L. variegatus to native sediment and overlying w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
21
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(23 citation statements)
references
References 25 publications
2
21
0
Order By: Relevance
“…The above findings are supported by recent studies employing in situ field chambers and ex situ laboratory exposures for the same sediments (Beckingham and Ghosh 2010; Janssen et al 2011). Using L. variegatus with PCB‐contaminated sediments from the Grasse River (near Massena, NY, USA), measured BSAFs from in situ and ex situ exposures were within a factor of 2 for 78 of the 80 PCB congeners studied (Beckingham and Ghosh 2010).…”
Section: Resultssupporting
confidence: 79%
See 1 more Smart Citation
“…The above findings are supported by recent studies employing in situ field chambers and ex situ laboratory exposures for the same sediments (Beckingham and Ghosh 2010; Janssen et al 2011). Using L. variegatus with PCB‐contaminated sediments from the Grasse River (near Massena, NY, USA), measured BSAFs from in situ and ex situ exposures were within a factor of 2 for 78 of the 80 PCB congeners studied (Beckingham and Ghosh 2010).…”
Section: Resultssupporting
confidence: 79%
“…The above findings are supported by recent studies employing in situ field chambers and ex situ laboratory exposures for the same sediments (Beckingham and Ghosh 2010; Janssen et al 2011). Using L. variegatus with PCB‐contaminated sediments from the Grasse River (near Massena, NY, USA), measured BSAFs from in situ and ex situ exposures were within a factor of 2 for 78 of the 80 PCB congeners studied (Beckingham and Ghosh 2010). Similarly, using L. variegatus with PCB‐contaminated sediments from Hunters Point (San Francisco, CA, USA), lipid‐corrected total PCB residues between in situ and ex situ exposures were within a factor of 2 (Janssen et al 2011).…”
Section: Resultssupporting
confidence: 79%
“…The effects of different AC types, doses, and particle sizes on bioaccumulation have been tested for a number of benthic invertebrates, zooplankton, macrophytes, and fish. The results showed that application of less than 4% of AC or similar carbonaceous materials lead to significant (i.e., up to 99%) decrease in bioaccumulation and in biota‐to‐sediment accumulation factors for invertebrates (West et al ; Jonker et al ; Sundelin et al ; Thorsen et al ; Zimmerman et al Zimmerman et al ; Millward et al ; Moermond et al ; Cho et al ; Cho et al ; Cho et al ; McLeod et al ; McLeod et al ; Sun and Ghosh ; Sun and Ghosh ; Tomaszewski et al ; Beckingham and Ghosh ; Beckingham and Ghosh ; Janssen et al ; Beckingham et al ; Kupryianchyk et al ; zooplankton (Kupryianchyk et al ;), macrophytes (Kupryianchyk et al 2013;), and fish (Shea et al ; Kupryianchyk et al ). Several recent studies reported up to 96% reduction in bioaccumulation of HOCs in benthic invertebrates when using AC as a capping material (Beckingham and Ghosh ; Lin et al ; Samuelsson ).…”
Section: Activated Carbon Applicationmentioning
confidence: 99%
“…Current approaches for risk assessment and management of aquatic contaminated sediment sites focus on the potential impacts of the contaminants of potential concern (COPCs) on the surrounding ecosystem [2,3]. …”
Section: Introductionmentioning
confidence: 99%
“…Several studies have investigated the bioavailability of HOCs to freshwater oligochaete worms to better assess remediation methods [2,715]. This paper presents an experimental study to assess the efficacy of capping using a thin sand cap (7.5 cm) and RCM to isolate PCB and naphthalene contaminated sediment from a model biouptake layer, and to reduce bioavailability as indicated using freshwater worms ( Lumbriculus variegatus ).…”
Section: Introductionmentioning
confidence: 99%